Compensation for Loss of Opportunity in Electronic Transactions: A Comparative Analytical Study in Light of Contemporary Digital Developments - Ibrahem Ali Hammadi; Salman Ali Humadi; Husham Hamed; Sameer Aboud Farhan; Kamil Sulaiman (Nusantara: Journal of Law Studies, 2026)
The rapid expansion of electronic commerce and digital technologies has generated new forms of civil liability, particularly concerning compensation for the loss of opportunity arising from electronic transactions. Existing legal frameworks, primarily developed for conventional contractual and tortious relationships, often fail to adequately address damages arising from technical failures, cybersecurity incidents, system disruptions, delayed electronic performance, and other digital risks. This study aims to examine the legal nature of compensation for loss of opportunity in electronic transactions, identify the legal requirements for establishing liability, analyse the evidentiary standards applicable to digital harm, and evaluate the principles governing the assessment of compensation. The research employs a comparative analytical methodology to examine legal doctrines, statutory provisions, and judicial precedents across the French, Egyptian, and selected Arab legal systems, particularly those of the United Arab Emirates and Jordan. The findings reveal that loss of opportunity constitutes an independent and legally compensable category of damage whenever a genuine and substantial probability of obtaining a benefit or avoiding a loss is interrupted by an electronically attributable fault. The study further demonstrates that compensation should be calculated based on the objective value of the lost opportunity rather than the total anticipated benefit, thereby preserving the proportionality between the interests of injured parties and the limits of civil liability. Moreover, the increasing reliance on digital evidence, electronic records, cybersecurity documentation, and technical expert testimony significantly strengthens the determination of causation and the assessment of damages in electronic transactions. This study contributes to the advancement of comparative civil liability scholarship by clarifying the legal framework governing compensation for digital loss of opportunity and by proposing a contemporary legal approach that enhances legal certainty, reinforces judicial consistency, strengthens consumer and commercial protection, and promotes greater confidence in electronic commerce amid the ongoing digital transformation.